New laboratory for over-the-air testing and wave field synthesis - Heuberger, Albert; et al. (Proceedings of the 30th URSI General Assembly, 2011)
In Ilmenau, Germany, a new laboratory is under construction for testing mobile communication equipment, both satellite and terrestrial. This contribution focuses on Over-The-Air testing of terrestrial mobile terminals and on applications of Wave Field Synthesis in this laboratory. The terrestrial research in the lab will mainly serve scientific purposes, as research into OTA test methodologies, also meant to actively engage in standardisation of OTA practices. Research into Wave Field Synthesis is another. A clear application is to study real-time antenna characteristics of mobile terminals in an OTA setting. With the projected equipment, a state-of-the-art OTA installation will become available. © 2011 IEE
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.komele.newlab